Analisis dan Prediksi IPK Berdasarkan Skor UTBK Menggunakan Algoritma Regresi Linier - Ilham Firman Ashari (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
Education is an important element that needs special attention, because education is an important element for the progress of a nation. Not only formal education starting from elementary school to high school, it can now be said that higher education has a central role in developing the capabilities of the Indonesian people. One way to get into state universities is with Ujian Tertulis Berbasis Komputer (UTBK). UTBK is set to be the main requirement to take part in the Seleksi Bersama Masuk Perguruan Tinggi Negeri (SBMPTN). Students' abilities cannot necessarily be measured by the UTBK scores. Student achievement when entering tertiary institutions is determined by an assessment of the GPA (Cumulative Achievement Index). In this study the authors tried to find a relationship between the UTBK scores and student GPAs using the linear regression method. The results showed that the correlation between the UTBK and GPA scores was 0.670157 and the mean squared error was 0.0546.